1999
DOI: 10.1016/s0167-2789(98)00274-7
|View full text |Cite
|
Sign up to set email alerts
|

Moving discrete breathers?

Abstract: We give definitions for different types of moving spatially localized objects in discrete nonlinear lattices. We derive general analytical relations connecting frequency, velocity and localization length of moving discrete breathers and kinks in nonlinear one-dimensional lattices. Then we propose numerical algorithms to find these solutions. Finally we discuss generalizations to higher dimensional lattices.Comment: 18 Pages, 5 figures,REVTEX. Citations and figures are added in this versio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…The numerical solution of the coupled DNLSEs (18)- (19), with the initial condition ψ (1)j (t = 0) = Ψ V j (t = 0) given by (20) and Λ = Λ sol , turns out to be in excellent agreement with (22) for different values of p, as shown in Fig. 2 for ω constant.…”
Section: B 1d Chainmentioning
confidence: 72%
See 1 more Smart Citation
“…The numerical solution of the coupled DNLSEs (18)- (19), with the initial condition ψ (1)j (t = 0) = Ψ V j (t = 0) given by (20) and Λ = Λ sol , turns out to be in excellent agreement with (22) for different values of p, as shown in Fig. 2 for ω constant.…”
Section: B 1d Chainmentioning
confidence: 72%
“…In 1D, the DNLSE is not integrable [17]; however, and as concerns the homogeneous case (V j = 0), solitonlike wavepackets exist and can propagate for a long time as stable objects, as it can be shown, e.g., by variational approaches [19,20]. Furthermore, the dynamics of such traveling pulses has been investigated in detail in the literature [21,22,23,24,25]. Based on the above discussion, here we consider the dynamics of a multicomponent BEC in an optical lattice described by a system of coupled DNLSEs, the different BEC components being different hyperfine levels [26].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed analysis of possible resonances has been carried out in [8,9]. It follows that one has to avoid resonances of the velocity V with phase velocities v ph of small amplitude plane waves (where the linear spectra which have been modified, as compared with the original underlying one).…”
Section: Why Only Time-periodic Orbits?mentioning
confidence: 99%
“…The question of the existence of moving solitons in the DNLS equation has been the subject of debate for some time [7,8,9,10,11,12,13,14,15,16,17,18,19]. Recently, Gómez-Gardeñes, Floría, Falo, Peyrard and Bishop [20,21] have demonstrated that the stationary motion of pulses in the cubic one-site DNLS (the 'standard' DNLS) is only possible over an oscillatory background consisting of a superposition of plane waves.…”
Section: Introductionmentioning
confidence: 99%